Netflix Originals dan Transnasionalisme SVOD: Analisis Jaringan Semantik di Indonesia dan Korea - Adiprabawa, Gentur (SOURCE : Jurnal Ilmu Komunikasi, 2024)
Fierce competition among subscription video on-demand (SVOD) service providers drives Netflix to increase new subscriber growth, where Indonesia and Korea are considered as countries with high potential. One of the transnational strategies carried out by Netflix is Netflix originals, which are films and series that produced through collaboration with local producers, and exclusively distributed by Netflix. Through semantic network analysis of 22 news articles of Netflix in Indonesia and 45 news articles of Netflix in Korea in the 2021-2023 period, this study reveals the Netflix’s idea of transnationalism in both countries. Several ideas were identified, which are related to localization of Netflix and their success in producing high quality of original contents that widely accepted by global audience. In general, it can be seen that news articles about Netflix originals are part of Netflix's strategy for their corporate branding as a leading global SVOD service provider. There are several indications of media framing carried out by Netflix to show a positive image behind their transnational strategy.